Decreased graft survival in liver transplant recipients of donors with positive blood cultures: a review of the United Network for Organ Sharing dataset. (28th December 2016) - Huaman, Moises A.; Vilchez, Valery; Mei, Xiaonan; Shah, Malay B.; Daily, Michael F.; Berger, Jonathan; Gedaly, Roberto
Summary: Liver transplantation using blood culture positive donors (BCPD) has allowed a significant expansion of the donor pool. We aimed to characterize BCPD and assess the outcomes of BCPD liver transplant recipients. We retrieved data from the United Network for Organ Sharing (UNOS) registry on all adults who underwent primary, single‐organ deceased‐donor liver transplantation in the USA between 2008 and 2013. Patients were classified into two cohorts: the BCPD cohort and the non‐BCPD cohort. One‐year graft and patient survival were compared between cohorts using Kaplan–Meier estimates and Cox models. A total of 28 961 patients were included. There were 2316 (8.0%) recipients of BCPD. BCPD were more likely to be older, female, black, diabetic, hypertensive, and obese compared to non‐BCPD. Graft survival was significantly lower in BCPD recipients compared to non‐BCPD recipients (Kaplan–Meier, 0.85 vs. 0.87; P = 0.009). Results remained significant in propensity‐matched analysis ( P = 0.038). BCPD was independently associated with decreased graft survival (adjusted HR; 1.10, 95% CI 1.01–1.20; P = 0.04). There were no significant differences in patient survival between study groups. BCPD was associated with decreased graft survival in liver transplant recipients. Studies are needed to identify subgroups of BCPD with the highest risk of graft failure and characterize the underlying pathogenic mechanisms.